1997
DOI: 10.1038/sj.jhh.1000444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma aldosterone to plasma renin activity ratio in patients with primary aldosteronism

Abstract: The plasma aldosterone to renin activity ratio (A/PRA) ratios in patients with primary aldosteronism were associated with unsuppressed plasma renin activity (PRA). was assessed retrospectively in 103 patients with primary aldosteronism including 74 patients with surgiAlthough the mean values of the A/PRA ratio differed significantly between the groups, complete separation cally proven adrenal cortical adenoma (APA) and 29 patients with idiopathic adrenal cortical hyperplasia was not obtained. The serum potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Furthermore, aldosterone production in Conn's adenoma in vivo relates to corticotropin secretion and this fact could question the 'autonomous' nature of aldosterone secretion which would explain why plasma aldosterone may not always be persistently elevated in some patients with APA. 14 …”
Section: The Controversy Of Idiopathic Hyperaldosteronismmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, aldosterone production in Conn's adenoma in vivo relates to corticotropin secretion and this fact could question the 'autonomous' nature of aldosterone secretion which would explain why plasma aldosterone may not always be persistently elevated in some patients with APA. 14 …”
Section: The Controversy Of Idiopathic Hyperaldosteronismmentioning
confidence: 99%
“…7 This explains the preponderance of PA cases due to Conn's adenoma by two-thirds to three-quarters over and above that of IHA in most PA series prior to the introduction of ARR as a screening test. 6,[13][14][15][16] However, with the shift in PA definition to that of assessing the lack of aldosterone suppressibility, IHA is more readily diagnosed and the use of ARR 7,17,18 as a screening tool has precipitated this. In fact, hypertensive patients with poorly suppressible aldosterone secretion in response to salt loading were described nearly three decades ago.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of screening for primary aldosteronism with the ARR, performed under random conditions with respect to salt intake is now well documented (28)(29)(30). However, there is no consensus regarding the indications for screening among hypertensives which takes into account recent reports of increased prevalence of primary aldosteronism using the ARR.…”
Section: Diagnosis Of Primary Aldosteronismmentioning
confidence: 99%
“…Patients with normotensive and subclinical PA may represent as an early, milder form of PA which may subsequently develop into hypertension on followup and lead to more aldosterone-dependent cardiovascular morbidity than essential hypertension [7, 8, 10]. Emerging evidence also has shown that PA patients may vary widely in their clinicolaboratory features [5], including atypical triad of normal PAC [6, 1114], nonsuppressed PRA [6, 11], and normal ARR [6, 11]. In addition, significant numbers of prehypertensive PA may have a subclinical picture [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant numbers of prehypertensive PA may have a subclinical picture [8, 9]. Moreover, low-renin hypertension and PA may also share elevated ARR [11, 13]. Thus, detection of the early or milder form of PA represents a particular challenge for clinicians.…”
Section: Introductionmentioning
confidence: 99%